Design And Manufacturing Of Formula Varsity Race Car Pedal System - Jamaludin, Mohd Zaini; Abdul Kudus, Syahibudil Ikhwan; Mohd Rosli, Mohd Afzanizam; Salim, Mohd Azli (2012)
This paper presents the design and manufacturing of a new pedal system for UTeM Formula Varsity race car. The new pedal was designed according to the rules and regulations for the Formula Varsity 2012. Through finite element analysis, the pedal design was found to be safe for operation. The prototype of the pedals was fabricated using 6061-Tb aluminum alloy material. The new end product was found to be 0.245 kg or 40% lighter than the previous design. The new pedal is expected able to perform successfully as per design requirement in the new 2012 UTeM.